KITAB "AL-BALAGHAH FI ILMI AL-BADII'" WA MUNASIBATUHU KA KITABI TA'LIMI AL-BALAGHAH LILSHOFI AS-SADISI BI MA'HAD DARUSSALAM GONTOR AL-HADISTI AL-MUADDALI BIL SHOFFI ATS-TSALIS LILMARHALAH AL-MUTAWASHITHAH - Muttaqin, Imam; Pimada, Luluk Humairo; Bakhet, Bakrie Mochammad (Borneo International Journal of Islamic Studies, 2020)
The article aims to evaluate book of Balaghoh fi Ilmi al-Badhi? by reviewing the elements of the content and the suitability to the condition and needs of Arabic language students in Indonesia. This book has been used in Pondok Modern Darussalam Gontor Ponorogo and several branch houses for learning the material of Balaghoh fi Ilmi al-Badhi? in general. This study will explain some criteria that are the basis for the evaluation process. Based on the research results, the researcher obtained an important point, namely this book is suitable for use by middle-level teachers, especially for sixth grade students (at Pondok Modern Darussalam Gontor Ponorogo and some branch houses). This book is used in learning so that the students can learn Balaghoh easily and gradually.